Intranasal administration of dsRNA analog poly(I:C) induces interferon-α receptor-dependent accumulation of antigen experienced T cells in the airways. - Beth McNally; Meredith Willette; Fang Ye; Santiago Partida-Sanchez; Emilio Flaño (PLoS ONE, 2012)
Polyriboinosinic-polyribocytoidylic acid (pIC), a synthetic dsRNA, acts as an adjuvant that boosts immune responses and protection. Intranasal (IN) administration of pIC has recently been used to adjuvant influenza virus vaccines; however, the effects of IN pIC administration on pulmonary T cell responses remain unclear. Here we show that a single IN administered dose of dsRNA into mice induced local Th1 chemokine production in the lungs and airways, and generated a biphasic and sustained migration of T lymphocytes to the airways. Furthermore, IN pIC-induced chemokine production and T cell recruitment to the airways were interferon-α receptor (IFNAR) signaling dependent. The effect of dsRNA on T cell recruitment to the airways was also dependent on the presence of high molecular weight (HMW) pIC, as a low molecular weight (LMW) pIC preparation known to only interact with TLR3 did not elicit the same effect on T cell migration to the airways, suggesting that the observed effects were dependent upon dsRNA recognition by multiple pattern recognition receptors (PPRs). IN pIC was additionally capable of stimulating low levels of T cell proliferation in the draining lymph nodes approximately 4-6 days after treatment that preceded a small population of de-novo T cells found in the airways by day 10. Taken together, these results demonstrate that the adjuvant effect of IN pIC that results in enhanced T cell proliferation and sustained T cell recruitment to the airways requires multiple PRRs and IFNAR signaling.